Community development participation scale: A development and validation study. Issue 4 (8th August 2021) - Gyan, Charles
ABSTRACT: This paper presents the development of a Community Development Participation Scale (CDPS) to be yieldingly administered and useful to community development researchers in measuring the level of participation of people in community development activities. This instrument was administered as a development and validation study to a sample of women from rural communities in Ghana ( N = 210). After the reliability and validity analysis, the attitude/interest subscale was left with eight (8) items and a Cronbach alpha level of .73. The active participation subscale was left with nine (9) items and a Cronbach alpha level of .79. Principal component analysis (PCA) with a direct oblimin rotation indicated a two-dimensional scale with a KMO value of .82 and a Bartlett's test of sphericity χ 2 (136) = 846.68, p < .01. These results show that the CDPS is strong enough to recommend its use in community development settings.